Methodology for Assessing the Harmony of Economic Relations Between Participants of the Agrofood Market - Kravchenko, Olha; Kucher, Anatolii; Yanchuk, Tetiana; Stavska, Yuliia (European Journal of Sustainable Development, 2020)
The purpose of the paper is to summarize the principles of harmonization of economic relations between participants of the agrofood market of Ukraine, in particular, the livestock products market, and to create a system of criteria for socio-ecological and economic assessment of the level of harmony of these relations with adherence to the principle of inclusivity. The results of a systematic review convincingly show that the basic principles of harmonization of economic relations between the livestock market participants shall be as follows: the principle of inclusivity, maximizing the mutual benefit of all parties to relationship, the consistency of their economic interests (or the principle of consensus), the principle of systematization, controllability, social fairness, openness and scientific validity. With the help of three indicator systems, namely: (1) criteria for assessing the socio-economic conditions of the livestock market entities, (2) criteria for assessing the development effectiveness and efficiency of the specified market entities, (3) criteria for assessing the harmonious relations of agricultural producers with other participants in relations on the product market animal husbandry, it is possible to systematically explore the economic environment in which modern economic relations between the livestock production market participants are formed, developed and transformed, and to find mechanisms for harmonizing such relations. Key words: economic relations, sustainable development, agrarian policy, harmonization, livestock products market, inclusivity, agrofood sector, Ukraine